Salivary High Sensitive C-Reactive Protein and Gingival Health Status among a Group of Women with Polycystic Ovary Syndrome (Mustansiria Dental Journal, 2019)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrinedisorder affecting women in their reproductive years. It is a complex disorderaffects not only general health but also show a reciprocal link with the oral health.C-reactive protein is an acute phase protein which increase their concentrationduring certain inflammatory disorders and used as a biomarker of inflammation inthe body. The aims of this study were to assess the gingival health status among agroup of women with polycystic ovary syndrome as well as to estimate the levelsof salivary high sensitive c-reactive protein in unstimulated saliva in relation togingival health condition.Materials and methods: Sixty two females with an age range 20-25 years old andwith a body mass index range18.5-24.9 (normal weight) were included in thisstudy. They were divided into two groups; the study group which included thirtyone females with polycystic ovary syndrome, those females attended BabylonTeaching Hospital/ Infertility Center with regular cycles, without clinical orbiochemical features of hyperandrogenism and ultrasound exclusion of polycysticovary (without polycystic ovary syndrome). Collection of unstimulated salivarysamples was carried out under standardrized conditions, salivary high sensitive creactiveprotein levels were estimated. Plaque index of Silness and Lӧe (1964)was used to assess dental plaque. While gingival index of Lӧe and Silness (1963)was used to assess gingival inflammation.Results: Results showed that the mean value of plaque index was found to be higherin the control group (1.18±0.03) than that in the study group (1.00±0.08) withstatistically highly significant difference (p